2015
DOI: 10.1186/s40645-015-0036-7
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemistry and limnology in Antarctic subglacial weathering: molecular evidence of the linkage between subglacial silica input and primary producers in a perennially ice-covered lake

Abstract: We report a 6,000 years record of subglacial weathering and biogeochemical processes in two perennially ice-covered glacial lakes at Rundvågshetta, on the Soya Coast of Lützow-Holm Bay, East Antarctica. The two lakes, Lake Maruwan Oike and Lake Maruwan-minami, are located in a channel that drains subglacial water from the base of the East Antarctic ice sheet. Greenish-grayish organic-rich laminations in sediment cores from the lakes indicate continuous primary production affected by the inflow of subglacial me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
2
8
1
Order By: Relevance
“…13 C, δ 15 N) δ 13 C and δ 15 S7 ). Their isotope ratios are consistent with the previously reported results regards to Lake Maruwan-oike pro les (Takano et al, 2015). On the other hand, vertical distribution of δ 13…”
Section: Elemental Data (Tc Toc Tn Tic and Ts)supporting
confidence: 92%
See 3 more Smart Citations
“…13 C, δ 15 N) δ 13 C and δ 15 S7 ). Their isotope ratios are consistent with the previously reported results regards to Lake Maruwan-oike pro les (Takano et al, 2015). On the other hand, vertical distribution of δ 13…”
Section: Elemental Data (Tc Toc Tn Tic and Ts)supporting
confidence: 92%
“…3). Based on the previous report (Takano et al 2015), the principal component analysis (e.g., Jolliffe and Cadima, 2016) and the correlation matrix tables for major elements in two lake sediments at Rundvagshetta (e. The conventional and calibrated ages of TOC in the Maruwanminami-ike sediment core is shown in Table 1. Age-depth relationship showed that sedimentation rates were slightly increased with depth (Fig.…”
Section: Lithology and Geochronologymentioning
confidence: 99%
See 2 more Smart Citations
“…To assess whether the sediments were deposited in freshwater, we determined sediment nitrogen isotopic composition using an elemental analyser (Costech 4010 or Flash 2000) − isotope ratio mass spectrometer (ThermoFinnigan, Delta Plus or ThermoFinnigan Delta V Advantage) as described by Takano et al . (). Nitrogen isotopic compositions are expressed as per mil (‰) deviations as: δ 15 N = [( 15 N/ 14 N) sample /( 15 N/ 14 N) standard −1] × 1000 (‰ vs .…”
Section: Methodsmentioning
confidence: 97%